2007
DOI: 10.1002/star.200700619
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Material and Tablet Formation Properties of four Dioscorea Starches

Abstract: The material and tablet formation properties of starches from four different Dioscorea species, namely White (D. rotundata), Bitter (D. dumetorum), Chinese (D. oppositifolia) and Water yam (D. alata), was characterized to determine their applicability as direct compression excipient. The physicochemical, thermal, morphological and material properties of the starches were investigated. The tablet formation properties were assessed using the 3‐D modeling parameters, the Heckel equation and the force‐displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 22 publications
4
55
0
2
Order By: Relevance
“…Crude fibre was not detected, while the crude fat of the starches ranged from 0.11 to 0.69%. Comparable values of crude fat for native yam starches (0.28-0.69%) have been reported (Rugchati and Thanacharoenchanaphas 2010;Odeku and Picker-Freyer 2007;Zuluaga et al 2007). Modification of the starches significantly reduced the crude fat contents.…”
Section: Chemical Composition Of Native and Modified Starchessupporting
confidence: 48%
See 4 more Smart Citations
“…Crude fibre was not detected, while the crude fat of the starches ranged from 0.11 to 0.69%. Comparable values of crude fat for native yam starches (0.28-0.69%) have been reported (Rugchati and Thanacharoenchanaphas 2010;Odeku and Picker-Freyer 2007;Zuluaga et al 2007). Modification of the starches significantly reduced the crude fat contents.…”
Section: Chemical Composition Of Native and Modified Starchessupporting
confidence: 48%
“…Native bitter yam starch had higher crude protein than other native yam starches, indicating that bitter yam starch granules may be more associated to protein bodies (Otto et al 1997) than the other yam starches. Comparable protein contents of 0.28-2.89% (Odeku and Picker-Freyer 2007), 3.23% (Aprianita et al 2009) and 1.22-2.27% (Olayinka et al 2011) has been reported for yams, Australian D. alata, and red and white sorghum starches, respectively. All modifications significantly reduced crude protein of the native starches.…”
Section: Chemical Composition Of Native and Modified Starchesmentioning
confidence: 87%
See 3 more Smart Citations